1999
DOI: 10.1164/ajrccm.160.5.9812031
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Lung Volume Change during Mechanical Ventilation

Abstract: To understand ventilator-induced lung injury (VILI) during positive pressure ventilation, mechanisms of normal alveolar mechanics must first be established. Isotropic "balloonlike" alveolar volume (VA) change has been viewed as the prevailing mechanism of normal lung volume (VL) changes. We hypothesized that change in VL is predominantly caused by alveolar recruitment-derecruitment (R/D). Fifteen mongrel dogs were anesthetized and intubated with a tracheal divider. Through a thoracotomy incision, in vivo micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
84
2
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(92 citation statements)
references
References 23 publications
4
84
2
2
Order By: Relevance
“…In the supine position, gravity causes the heart to be suspended from the sternum, occupying a larger space in the anterior compartment, whereas in the prone position, the heart is resting on the sternum, allowing more anterior lung expansion. Our EIT data set will provide a valuable comparison for future studies in subjects with lung disease or during mechanical ventilation, where alveolar recruitment and derecruitment during tidal breathing can occur [26,[28][29][30].…”
Section: Image Analysismentioning
confidence: 99%
“…In the supine position, gravity causes the heart to be suspended from the sternum, occupying a larger space in the anterior compartment, whereas in the prone position, the heart is resting on the sternum, allowing more anterior lung expansion. Our EIT data set will provide a valuable comparison for future studies in subjects with lung disease or during mechanical ventilation, where alveolar recruitment and derecruitment during tidal breathing can occur [26,[28][29][30].…”
Section: Image Analysismentioning
confidence: 99%
“…Because most fixatives affect tissue hydration and surface tension and thereby distort lung architecture relative to its in vivo state, the current models of alveolar micromechanics await morphometric confirmation on living, unfixed specimens (48). Microscopic imaging of canine subpleural alveoli through a pleural window suggested that alveolar volume changes little during normal breathing (49) and that the acinus expands nonuniformly (43). Because the mechanics of subpleural alveoli may be dominated by their coupling to a relatively inelastic pleural membrane, which in these experiments had to be immobilized to generate a focused image, the amplitude of alveolar volume change during quiet breathing is likely to remain a topic of active investigation.…”
Section: Alveolar Micromechanics Of the Normal Lungmentioning
confidence: 99%
“…Intravital microscopy has been used to visualize alveolar structures (11)(12)(13)(14)(15)(16), but these techniques are also limited by the ability to visualize only subpleural structures and the invasive nature of the technique. As pointed out by Hubmayr (17), there is relatively little consensus about alveolar deformation during breathing.…”
mentioning
confidence: 99%